Utilization of preventive care services and their effect on cardiovascular outcomes in the United States - Varun Vaidya; Gautam Partha; Jennifer Howe (Dove Medical Press, 2011)
Varun Vaidya, Gautam Partha, Jennifer HowePharmacy Health Care Administration, Department of Pharmacy Practice, University of Toledo College of Pharmacy, Toledo, OH, USAObjective: To describe and analyze utilization of preventive care services and their effect on cardiovascular outcomes in the United States.Methods: Data from the 2007 Medical Expenditure Panel Survey (MEPS) were used to analyze utilization of preventive care services and their effect on cardiovascular outcomes. Recommendations by the Seventh Report of the Joint Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure and the National Cholesterol Education Program were used to determine appropriate levels of preventive care utilization. Utilization of blood pressure screening and cholesterol checkup services were used as the dependent variable, while age, gender, race, ethnicity, insurance status, and perceived health status were used as independent variables. Since guidelines differ for people with elevated blood pressure, respondents with elevated blood pressure were identified in the MEPS database by self-reported diagnosis. Descriptive statistics were used to describe the population, while a multivariate logistic regression model was built to predict odds of utilizing appropriate levels of preventive services.Results: Total number of adult respondents for which data were available for blood pressure checkup and cholesterol checkup was 20,523 and 15,784, respectively. Overall, MEPS respondents were found to adhere to guideline recommendations for preventive care utilization. Multivariate logistic regression showed that odds of utilization of preventive care services were higher for elderly patients (age >65 years) for blood pressure (odds ratio [OR] = 2.39, 95% confidence interval [CI]: 1.92–2.97) and cholesterol (OR = 3.05, 95% CI: 2.18–4.27) preventive services compared with younger population (age 18–54 years). Males had much lower odds of getting blood pressure (OR = 0.33, 95% CI: 0.30–0.37) and cholesterol (OR = 0.59, 95% CI: 0.50–0.70) checks done compared with females. Odds of utilization were nearly similar for all races. Uninsured had lower odds for blood pressure (OR = 0.26, 95% CI: 0.23–0.30) and cholesterol (OR = 0.30, 95% CI: 0.24–0.39) checks compared with privately insured people. Asians had lower odds of getting blood pressure checkups compared to Whites (OR = 0.49, 95% CI: 0.39–0.63). Similar trends were recorded for other covariates such as race and perceived health status.Conclusion: The study was successful in identifying existing age, race, income, and insurance-status related disparities in preventive care utilization within a US population.Keywords: guidelines, prevention/screening, gender differences in health and health care, racial/ethnic differences in health and health care